Effect of electric field on the ultrasonic wave propagation velocity in oils - SKUMIEL, A.; ŁABOWSKI, M. (Archives of Acoustics, 1990)
A dielectric liquid in an external electric field exhibits variations in its physical properties as a result of deformational polarisation and orientational polarisation. Moreover, it undergoes volume deformation due to electrostriction. The present work represents an attempt at a quantitative description of ultrasonic wave propagation in a dielectric liquid acted on by a transversal electric field. Our search for a functional dependence between the propagation velocity c_E and the external field strength E was based on the change in free energy of the medium under the action of the field. We derive general expressions valid with regard to polar as well as non-polar dielectrics for the square of the propagation velocity and compare them with our experimental results, obtained by the phase method for some selected oils. Moreover, we determine the electrostrictional change in density of the medium in the external field for field strengths applied in experiments as well as for their maximal values close to breakdown. Finally, we perform an analysis of our experimental results in face of the theoretical predictions and propose a new mechanism as responsible for the behaviour of the dielectric in the electric field.